2017
DOI: 10.1186/s12931-017-0566-1
|View full text |Cite
|
Sign up to set email alerts
|

Rescue medication use as a patient-reported outcome in COPD: a systematic review and regression analysis

Abstract: BackgroundReducing rescue medication use is a guideline-defined goal of asthma treatment, however, little is known about the validity of rescue medicine use as a marker of symptoms in chronic obstructive pulmonary disease (COPD). To improve patient outcomes, greater insight is needed into the relationship between rescue medication use and alternative COPD outcomes.MethodsA systematic search of electronic databases (Embase®, MEDLINE® and Cochrane CENTRAL) was conducted from database start to 26 May, 2015. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“… 12 , 13 Rescue medication use is an important indicator of disease severity and exacerbation risk. 8 11 , 14 In a systematic review including 46 studies reporting rescue medication use and other outcomes in patients with COPD, rescue medication use was negatively correlated with lung function and dyspnea and positively correlated with health status over 6 months. 8 A retrospective claims-based study of patients with COPD diagnoses showed a relationship between filled prescriptions for rescue medications and exacerbations over 1 year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 Rescue medication use is an important indicator of disease severity and exacerbation risk. 8 11 , 14 In a systematic review including 46 studies reporting rescue medication use and other outcomes in patients with COPD, rescue medication use was negatively correlated with lung function and dyspnea and positively correlated with health status over 6 months. 8 A retrospective claims-based study of patients with COPD diagnoses showed a relationship between filled prescriptions for rescue medications and exacerbations over 1 year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to inhaled maintenance therapy is critical to the management of COPD symptoms. 5 – 7 Greater rescue medication use is associated with worse lung function, more severe COPD symptoms, impaired health status, and increased risk of exacerbations; 8 11 therefore, it may be considered a marker of inadequate treatment or treatment adherence. Medications associated with increased adherence and reduced rescue medication use may, therefore, provide better control of COPD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…2 In a recent meta-analysis of 46,531 patients from 46 studies, rescue medication use correlated with clinically important COPD outcomes, including trough forced expiratory volume in 1 second (FEV 1 ), St. George's Respiratory Questionnaire (SGRQ), and annualized moderate or severe exacerbation rates. 3 While many studies have assessed the impact of treatment on rescue medication use, there are limited analyses of the impact of the level of rescue medication use at baseline on the efficacy and safety of longacting bronchodilators in patients with COPD. In one such analysis, patient stratification based on baseline use of rescue medications did not impact the efficacy and safety of QVA149 compared with placebo or salmeterol/fluticasone combination.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this pairwise meta-analysis confirm that doxofylline is effective and safe when administered to COPD patients. Compared to the control, doxofylline significantly improves lung function and dyspnea, and reduces the daily use of rescue medication more than the proposed minimal clinically important difference (MCID) values for COPD outcomes [42]. Similarly to all xanthines, it induces some AEs, but they are mild in severity.…”
Section: Discussionmentioning
confidence: 93%